1981
DOI: 10.1103/physrevlett.46.1111
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Dibaryon Resonances inI=1,D21

Abstract: Recent, precise analyses of p-p and n~p scattering data up to 800 MeV by Arndt et at. have provided the strongest evidence to date for the existence of dibaryon states in the 7 = 1, D 2 and 3 F 2 nucleon-nucleon channels. Model fits to their new phases reveal poles located near the "NA" threshold (2.15 -0.05i GeV). Because of their strong coupling to this channel, these dibaryon resonances are highly inelastic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
17
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(24 citation statements)
references
References 12 publications
7
17
0
Order By: Relevance
“…Refs. [61][62][63][64][65][66][67][68][69][70][71][72]. Since in this route D 12 and the associated pion have to be in relative p-wave, in order to fulfill the angular momentum requirements of D 03 , this decay route is practically indistinguishable from the route D 03 → ∆∆ → dππ, i.e.…”
Section: ∆∆ Final State Interactionmentioning
confidence: 99%
“…Refs. [61][62][63][64][65][66][67][68][69][70][71][72]. Since in this route D 12 and the associated pion have to be in relative p-wave, in order to fulfill the angular momentum requirements of D 03 , this decay route is practically indistinguishable from the route D 03 → ∆∆ → dππ, i.e.…”
Section: ∆∆ Final State Interactionmentioning
confidence: 99%
“…The possible existence of this resonance was confirmed in the sixties by Dick Arndt [28] analyzing pp scattering data. Later-on, in the eighties and nineties, the SAID data analysis group could demonstrate [29][30][31][32] by partial wave anaylses based on high-quality data for pp → pp, πd → πd and πd → pp that the 1 D 2 partial wave exhibits a pronounced looping in the Argand diagram -in favor of a genuine s-channel resonance. However, since the mass of the resonance is close to the NΔ threshold and since in addition the width of the resonance is compatible with that of the Δ, it has been argued that the observed features represent a NΔ threshold phenomenon rather than a s-channel resonance and the observed looping in the Argand plot is just a reflection of the usual Δ excitation.…”
Section: A Remnant From This Period -A Resonance In Thementioning
confidence: 99%
“…1) and 2). *) The K-matrix elememts are parametrized as the polynomials in the squared cms energy s, (3) Preliminary analysis suggested that we need at least M = 2 to fit the input amplitudes. We fix M at 2 in this analysis.…”
Section: K-matrix Simulation Of the Experimental Amplitudesmentioning
confidence: 99%
“…Dibaryon-pole searches by the two-channel (pp, NLl) K(M)·matrix approach were performed by Edwards and. Thomas,),2) and by Bhandari et al 3) They have found poles in the area suggested by the single-channel analyses in terms of the Breit-Wigner formula. Among criticisms cast upon these K-matrix analyses, one important but not fully examined point is the validity of the two-channel approximation.…”
mentioning
confidence: 91%